Clinical significance of circulating tumor cells in predicting disease progression and chemotherapy resistance in patients with gestational choriocarcinoma. Issue 6 (26th October 2018) - He, Weiling; Hou, Minzhi; Zhang, Hui; Zeng, Chao; He, Shanyang; Chen, Xinlin; Xu, Manman; Sun, Cong; Jiang, Wenting; Wang, Han; Shen, Hongwei; Zhang, Yang; et al.
Abstract : Gestational choriocarcinoma (GC) is a highly aggressive tumor. In our study, we systematically investigated EpCAM/CD147 expression characteristics in patients with GC and assessed the role of circulating tumor cells (CTCs) in predicting chemotherapy response and disease progression. GC tissues were positive for either epithelial cellular adhesion molecule (EpCAM) or CD147, and all samples exhibited strong human chorionic gonadotropin (HCG) expression. Among all the recruited patients ( n = 115), 103 had at least 1 CTC in a 7.5‐mL peripheral blood sample, and the percentage of patients with ≥4 CTCs in a particular FIGO stage group increased with a higher FIGO stage ( p < 0.001). Furthermore, the pretreatment CTC count was related to tumor size ( r = 0.225, p = 0.015) and the number of metastases ( r = 0.603, p < 0.001). A progression analysis showed that among the 115 included patients who qualified for further examination, 52 of the 64 patients defined as progressive had ≥4 pretreatment CTCs, while only 7 of the 51 non‐progressive patients had ≥4 pretreatment CTCs ( p < 0.001). In multivariate analysis, CTCs (≥4) remained the strongest predictor of PFS when other prognostic markers, FIGO score and FIGO stage were included. Moreover, based on the chemotherapy response, patients with ≥4 CTCs were more likely to be resistant to chemotherapy than those with <4 CTCs ( P < 0.001). These findings demonstrates the feasibility of CTC detection in cases of GC by adopting EpCAM/CD147 antibodies together as capturing antibodies. The CTC count is a promising indicator in the evaluation of biological activities and the chemotherapy response in GC patients. Abstract : What's new? Gestational choriocarcinoma tumor cells tend to spread to distant organs by hematogenous dissemination. This study shows that circulating tumor cells (CTCs) in patients with gestational choriocarcinomas can be readily captured by targeting the highly expressed membrane antigens EpCAM and CD147. Elevated CTC levels, defined as 4 or more CTCs per 7.5 ml of peripheral blood, were found to predict chemotherapy resistance and to more effectively predict disease progression where compared with traditional β‐human chorionic gonadotropin. The findings suggest that CTC enumeration could be used to stratify gestational choriocarcinoma patients for personalized clinical intervention.